Uso de las redes sociales y su incidencia en la autoestima de los estudiantes del bachillerato de la Unidad Educativa Nicolás Infante Díaz en el cantón Quevedo, año 2021 - Espinal Cedeño, Edgar Alexander (2022)
The following research paper deals with social networks and their impact on the self-esteem of high school students of the Nicolas Infante Díaz educational unit, currently networks are usually a little addictive, but this depends on how you use it and what you are going to do on them, many times high school students think that social networks are just that, "social networks" but no, they are extremely wrong, social networks provide us with some contact with people we have not seen for a long time, in part that is good, but this is where communication and interaction with parents prevails, social networks should be supervised and controlled by them, since their children can be victims of any problem that this exerts on those students, networks can give us a radical turn in our lives, as many of us know